Anaerobic digestion of cheese whey using acclimatized granular sludge at moderately low ph and zero-valent iron addition - Charalambous, Panagiotis (My University, 2024)
Cheese whey (CW), a major by-product of cheese manufacturing, is ideal for anaerobic degradation and bioenergy production due to its high biodegradability and significant carbohydrate content, which makes up over 70% of its organic matter. Aligned with the circular economy concept, anaerobic digestion (AD) is a sustainable technology that can exploit the high organic matter (50–102 g/L COD) of CW and generate value-added products, such as biogas and fertilizer. However, its rapid acidification due to volatile fatty acids (VFAs) accumulation coupled with an inherent lack of natural alkalinity (<0.22 gCaCO3/L) resulted in a pH drop, which negatively affects methanogenesis and the process's stability. To date, various methods have been proposed to handle the problematic AD of CW targeting to mitigate VFAs accumulation and improve the process stability. Dosing alkaline agents (NaOH or NaHCO3), co-digestion of CW with rich alkaline substrates, or the two-stage anaerobic digestion process, have been proposed to overcome acid inhibition and to ensure a stable monitoring of the process. However, most of these technologies are cost-effective in terms of operation and chemical additives. Therefore, alternative, cost-efficient technologies to enhance the anaerobic digestion of CW are needed. This research study proposes two alternative strategies to alleviate acid inhibition and improve the performance of AD of CW.
Keywords: Acclimatized granular sludge at pH 5-6; Anaerobic digestion; Biogas upgrading; Cheese whey; VFA degradation; Zero-valent iron